The Role of Recreational Physical Activity in Adherence to the Mediterranean Diet in the Greek Population: Public Health and Sustainability Implications - Ioannis Tsartsapakis; Ioannis Trigonis; Aglaia Zafeiroudi; Olga Kouli; Vasileios Papacharisis; Dionisis Stavrousis (Sports)
The Mediterranean diet (MedDiet) is renowned for its health benefits and cultural significance in Mediterranean populations. The present study investigates the question of whether individuals who participate in recreational activities exhibit higher adherence to the MedDiet than those who do not engage in such activities. A cross-sectional survey was conducted with participants completing questionnaires assessing demographic characteristics, MedDiet adherence, and dietary habits. A total of 1055 participants of both sexes with an average age of 32.2 ± 10.1 years participated in the survey, and they were classified based on their engagement in recreational physical activity. Statistical analyses included independent samples t-tests, chi-squared tests, analysis of variance (ANOVA), and multiple regression analysis. The results demonstrated that physically active individuals exhibited significantly higher adherence to the MedDiet than non-exercisers (p < 0.001), supporting the hypothesis that exercise is associated with healthier dietary choices. Regression analysis further revealed that exercise, olive oil consumption, and family meals were significant predictors of MedDiet adherence. Additionally, group comparisons highlighted differences in BMI (p < 0.001), meal frequency (p < 0.001), and food preparation habits (p < 0.001), indicating that exercisers were more likely to adopt a holistic Mediterranean lifestyle. These findings emphasize the importance of integrating physical activity with dietary education in public health policies. Promoting an active lifestyle alongside MedDiet principles may enhance overall well-being and contribute to sustainable health strategies.